Role of mosaic aneuploidy in the development and progression of Huntington's disease: Developing topics. (7th December 2020) - Elos, Mihret; Caneus, Julbert; Ahmed, Md Mahiuddin; Markham, Neil; Chial, Heidi J; Potter, Huntington
Abstract: Background: Huntington disease (HD) is an autosomal dominant neurodegenerative disorder caused by a CAG trinucleotide repeat expansion mutation in the huntingtin ( HTT ) gene. HTT encodes the huntingtin protein, which has been shown to localize to spindle poles and is required for proper mitotic spindle orientation, chromosome segregation, and cell cycle regulation. Mutations in HTT lead to the production of a mature huntingtin protein with an expanded polyglutamine region (>35 repeats) at its N terminus. Previous studies have shown that mouse models of HD exhibit defects in microtubule function and in cell cycle regulation. HD is a progressive condition characterized by decline in cognitive and executive functions. Over the years, studies from our laboratory and others have shown elevated levels of aneuploidy in many neurodegenerative disorders that are characterized by cognitive deficits, including Alzheimer's disease (AD) and frontotemporal lobar degeneration (FTLD). Here, we investigated whether chromosome segregation defects that lead to mosaic aneuploidy and consequent apoptosis may also contribute to neuronal loss in HD. Method: Single cell suspensions were prepared from human brain samples (cortex and cerebellum) and fibroblast cell lines from HD donors and age‐matched controls and were processed for FISH analysis of human chromosome 21, NeuN immunostaining, and/or TUNEL staining. Single cell suspensions from cerebellum were prepared from mouse models of HD and age‐matched controls for FISH analysis of mouse chromosome 5 or 16, which is syntenic to human chromosome 21. Result: We observed increased levels of mosaic aneuploidy and associated apoptosis in brain tissues and in cultured fibroblasts from HD donors compared to age‐matched controls. We also observed increased levels of mosaic aneuploidy in brain tissue from HD mice compared to age‐matched controls. Conclusion: Together with our previous studies of AD and FTLD, these data provide evidence that chromosome segregation defects that lead to genomic instability may serve as a shared mechanism underlying many neurodegenerative disorders. Our findings highlight the need to further investigate the biological mechanism(s) underlying HD pathology and set the stage for novel therapeutic approaches to HD that may also be applied to other neurodegenerative disorders.